2020
DOI: 10.1002/pds.5020
|View full text |Cite
|
Sign up to set email alerts
|

Quality of reporting of drug exposure in pharmacoepidemiological studies

Abstract: Purpose Exposure definitions vary across pharmacoepidemiological studies. Therefore, transparent reporting of exposure definitions is important for interpretation of published study results. We aimed to assess the quality of reporting of exposure to identify where improvement may be needed. Method We systematically reviewed observational pharmacoepidemiological studies that used routinely collected health data, published in 2017 in six pharmacoepidemiological journals. Reporting of exposure was scored using 11… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 35 publications
0
7
0
Order By: Relevance
“…Determining medicine exposure periods is critical in pharmacoepidemiological research for exposure‐outcome studies and in quantifying persistence and adherence to treatment. Pharmaceutical claims (i.e., dispensing) data are often used as a key information source for defining medicine exposure periods 1 . In many jurisdictions, including across Europe 2 and Australia, 3 however, pharmaceutical claims data do not record information on exact indications, directions for use, or the intended duration of medicine supply.…”
Section: Introductionmentioning
confidence: 99%
“…Determining medicine exposure periods is critical in pharmacoepidemiological research for exposure‐outcome studies and in quantifying persistence and adherence to treatment. Pharmaceutical claims (i.e., dispensing) data are often used as a key information source for defining medicine exposure periods 1 . In many jurisdictions, including across Europe 2 and Australia, 3 however, pharmaceutical claims data do not record information on exact indications, directions for use, or the intended duration of medicine supply.…”
Section: Introductionmentioning
confidence: 99%
“…We observed this most often in the assessment of bias due to missing data. This poor reporting is not specific to COVID‐19 research and has also been observed for pharmacoepidemiologic studies in general 30,31 . Understandably, due to word limits, authors are unable to elaborate on all methodological decisions in their manuscript.…”
Section: Discussionmentioning
confidence: 99%
“…This poor reporting is not specific to COVID-19 research and has also been observed for pharmacoepidemiologic studies in general. 30,31 Understandably, due to word limits, authors are unable to elaborate on all methodological decisions in their manuscript. However, in situations where methods deviate from generally accepted methods, substantiation of choices that were made is needed for correct interpretation of the results of a study as well as for assessment of its validity.…”
Section: Summary Of Findingsmentioning
confidence: 99%
“…24 While the implementation of these definitions will depend on the specific data source, the basic considerations are similar across Europe, Asia and North America. 24 Differences across sites in their definitions of these events are likely to have contributed to the large variation in study measures observed in our study. Although we provided detailed descriptions of these treatment events in the initial shared protocol, each site had a different approach to operationalization of these events (Table 1).…”
Section: Discussionmentioning
confidence: 99%